Answer:
D. SAS
Step-by-step explanation:
Given: ΔABC
Bisecting <ABC to create point D implies that BD is a common side to ΔABD and ΔCBD.
Also,
m<ABD = m<CBD (angle bisector)
BA = BC (given property of the isosceles triangle)
Therefore,
ΔABD ≅ ΔCBD (Side Angle Side)
The reason for statement 5 in this proof is that ΔABD ≅ ΔCBD by SAS (Side-Angle-Side) relations of the congruent triangles.
What do you mean
<span>How to move from fractions as a part to whole to ratios?</span>
If you would like to divide 3 and 1/6/(-9), you can do it using the following steps:
3 / 1/6/(-9) = 3/1 / 1/6/(-9) = 3/1 * (-9)/1/6 = -27 / 1/6 = -27 * 6 = -162
The result you get is -162.
It’s -4 and it’s -5.........